Effect of endurance training on the lactate and glucose minimum intensities - Junior, Pedro Balikian (2018)
Due to the controversy about the sensitive of lactate minimum intensity (LMI) to training and the need to develop other tool for aerobic fitness evaluation, the purpose of this study was to analyze the sensitivity of glucose minimum intensity (GMI) and LMI to endurance training. Eight trained male cyclists (21.4 ± 1.9 years, 67.6 ± 7.5 kg and 1.72 ± 0.10 m) were evaluated twice, before and after 12 weeks of training. GMI and LMI were calculated, respectively, by the lowest blood glucose and lactate values attained during an incremental test performed after a hyperlactemia induction, and VO2max was determined during standard incremental effort. The training was prescribed in three different zones and controlled by heart rate (HR). The training distribution was equivalent to 59.7%, 25.0% and 15.3% below, at and above anaerobic threshold HR respectively. The anaerobic threshold evaluated by GMI and LMI improvement 9.89 ± 4.35% and 10.28 ± 9.89 respectively, after training, but the VO2max 2.52 ± 1.81%. No differences were found between GMI and LMI in pre (218.2 ± 22.1 vs 215.0 ± 18.6 W) and post (240.6 ± 22.9 vs 237.5 ± 18.8 W) training situations. LMI and GMI were sensitive to 12-week aerobic training in cyclist; thus, both protocols can be used to assess aerobic adaptation, athletes diagnostic and prescribe training.